Pengaruh Implementasi Digital Marketing Terhadap Peningkatan Volume Penjualan UMKM Smille Bouquet Di Desa Kedungdalem - Taufikurrahman Taufikurrahman; Afifah Ulul Azmi; Dinda Griselda Azura Gestyaki; Dhiya' Ayu Adibah; Rachmanita Eza Putri Wiyandari; Thersa Armenia Putri (Universitas 17 Agustus 1945 Semarang, 2023)
Technological developments in the current industrial era 4.0 are inevitable, especially in the business sector. The rapid dissemination of information has an impact on the process of the business itself. This is the most important point for business people, starting from the increase in sales volume and profits from usual. Digital marketing is one of the marketing media to market businesses in the form of services, labor, and others that are now in great demand by the wider community. Therefore with digital marketing, it can make it easier for people to run their business with marketing and sales techniques that are different from before. Advances in technology, especially in the field of information create new concepts in the field of marketing. The Smille Bouquet (SME) Small and Medium Enterprise actor from Kedungdalem Village initially carried out offline marketing which was carried out by marketing sales during graduation events, as well as other events that could be visited to market the bouquet. However, entering this digital marketing era, Smille Bouquet (SME) Small and Medium Enterprise actors also take advantage by marketing through social media such as Instagram, Shopee and Whatsapp. Smille Bouquet (SME) Small and Medium Enterprise choose online marketing or take advantage of digital marketing because it can increase sales volume and develop the business so that it is better known by the wider community.